OPTIMALISASI PERENCANAAN SISTEM DRAINASE RUMAH SAKIT (STUDI KASUS RS PERMATA PALEMBANG) - Ananda, Putri; Firdaus, Muhammad; Purwanto, Herri (Fakultas Teknik, Universitas Wiraraja, 2025)
The proper drainage system design an important aspect in the development of healthcare facilities such as Permata Palembang Hospital. This study aims to analyze the suitability of the hospital drainage system design with applicable standards, and to evaluate the channel capacity to accommodating water discharge from the hospital and runoff from Citra Bukit Lestari Housing Area before operation. The analysis methods include calculation of statistical parameters, design rainfall distribution, distribution suitability test, rainfall intensity, peak flood discharge, and channel dimensions. The results of the analysis indicate that the initial design did not take into account the rainfall factors and design flood discharge. The evaluation of existing channel capacity shows sufficient capacity for U Ditch 1 channel, however the capacity of 3 box culvert channels and 4 box culvert channels is not enough to accommodate peak discharge. The optimization was carried out by redesigning the channel dimensions, widening the 3 box culvert channel to 550x400 mm and 4 box culvert to 1000x800 mm. This redesign results in a channel capacity that is able to accommodating design flood discharge, both under normal and extreme conditions.